A Study to Evaluate the Effect of Chyavanprash in Elderly People Having Low Vital Capacity (International Journal of Ayurveda and Pharma Research, 2022)
Ageing is a natural process. Senescence is an expression used for the deterioration in the vitality or the lowering of the biological efficiency that accompanies ageing. Respiratory system undergoes various anatomical, physiological and immunological changes with age. Lungs mature at age 20 to 25 years, and then it decreases about 200 to 250cc every 10 years from 20 years of age. Among elderly health problems, respiratory conditions make 16.1% of the complaints. Chyavanprash, one of the foremost Rasayana is specifically indicated for elderly people. This would be the remedy for improving the respiratory system functioning in aged people, if it could prove the effect in enhancing the vital capacity. Individuals of age 50 years and above were screened by using computerized spirometer. From these, 67 individuals with reduced vital capacity were selected for the study. Spirometric assessment was done. After the assessment, Chyavanprash was administrated. Dosage was fixed as 10gm for a period of 1 month. After 1 month spirometric assessment was done. This shows that there exists a positive response in vital capacity to Chyavanprash. Rasayana, Brmhana, Tridoshahara, and Balya properties evoked a positive response in vital capacity.